For All These Rights : Business, Labor, and the Shaping of America's Public-Private Welfare State. - Klein, Jennifer (Princeton University Press, 2010)
The New Deal placed security at the center of American political and economic life by establishing an explicit partnership between the state, economy, and citizens. In America, unlike anywhere else in the world, most people depend overwhelmingly on private health insurance and employee benefits. The astounding rise of this phenomenon from before World War II, however, has been largely overlooked. In this powerful history of the American reliance on employment-based benefits, Jennifer Klein examines the interwoven politics of social provision and labor relations from the 1910s to the 1960s. Thr.